2023
DOI: 10.1158/1078-0432.ccr-23-0488
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Therapy Induces Receptor-Dependent DNA Damage Enhanced by PARP Inhibition in ER+ Breast Cancer

Abstract: Purpose: Clinical evidence indicates that treatment with estrogens elicits anti-cancer effects in ~30% of patients with advanced endocrine-resistant estrogen receptor alpha (ER)-positive breast cancer. Despite the proven efficacy of estrogen therapy, its mechanism of action is unclear and this treatment remains under-utilized. Mechanistic understanding may offer strategies to enhance therapeutic efficacy. Experimental Design: We performed genome-wide CRISPR/Cas9 screening and transcriptomic profiling in long-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Extending our findings to potential explanations for mechanisms of endocrine resistance, it has been observed that elevated levels of ER can promote resistance to estrogen deprivation and even promote therapeutic sensitivity to estrogen treatment [ 49 , 50 ]. For patients with ER+ breast cancer exhibiting high levels of TRIM33 and ER, TRIM33 inhibition may be considered a therapeutic opportunity to downregulate ER and prevent estrogen-independent tumor growth, as is observed upon resistance to aromatase inhibitor therapy.…”
Section: Discussionmentioning
confidence: 91%
“…Extending our findings to potential explanations for mechanisms of endocrine resistance, it has been observed that elevated levels of ER can promote resistance to estrogen deprivation and even promote therapeutic sensitivity to estrogen treatment [ 49 , 50 ]. For patients with ER+ breast cancer exhibiting high levels of TRIM33 and ER, TRIM33 inhibition may be considered a therapeutic opportunity to downregulate ER and prevent estrogen-independent tumor growth, as is observed upon resistance to aromatase inhibitor therapy.…”
Section: Discussionmentioning
confidence: 91%
“…Our method demonstrated superior performance in both real-world studies and simulated datasets, and it imposes no constraint on tumor growth kinetics and uses TV data from all days for all mice. Our method is based on eGR, an unbiased metric of in vivo antiproliferative drug effect ( 30 ), which is similar to two unbiased metrics of in vitro antiproliferative drug effect, the DIP rate proposed by Harris and colleagues ( 33 ), and the drug-induced GR inhibition by Hafner and colleagues ( 32 ), and it offers an easy algebraic way for calculating GR for in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms include induction of the unfolded protein response (UPR), activation of the extrinsic-death receptor pathway and intrinsic-mitochondrial pathway and downregulation of pro-survival, cell-growth pathways. Recently, it was reported that estrogen induces DNA damage in long-term estrogen-deprived (LTED) ER+ breast cancer models and offers a potential pathway that can be exploited therapeutically [43]. The establishment of laboratory models of endocrine resistance, including cell lines in 2D and 3D, cell-linederived xenografts (CDXs) and patient-derived xenografts (PDXs), was fundamental to our understanding of the molecular mechanism of E2-induced inhibition.…”
Section: Molecular Mechanisms Of Estrogen-induced Tumor Regressionmentioning
confidence: 99%
“…In MCF-7 cells, E2 induces genomic instability via the formation of ER-dependent R-loops [79]. A recent study conducted genome-wide CRISPR/Cas9 screening and transcriptome profiling of LTED HCC1428 breast cancer cells and determined that E2 induces DNA damage mediated via transcriptional activation of the ER [43]. The molecular mechanism by which E2 induces DNA damage involves the formation of R-loops, which are hybrid DNA-RNA structures formed when nascent mRNA re-anneals to the template DNA strand (Figure 3).…”
Section: Estrogen Induces Receptor-dependent Dna Damage In Er-positiv...mentioning
confidence: 99%